Uses of financial information in bank lending decisions - Stephens, Ray G. (Ann Arbor, Mich. : UMI Research Press, 1980)
This research reported a study that arose out of a desire to use accounting information by bank lending officers to determine factors in decision making.
Includes index.
Includes bibliographical references: p. [325]-331
asm 23/01/2018
Loans
Keywords: Bank loans--Decision making; Financial statements; Disclosure in accounting